2015
DOI: 10.15835/nsb.7.3.9616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Generic Extended-Spectrum β-Lactam-Resistant Enterobacteria in Healthy Pigs

Abstract: This study was conducted to isolate generic extended-spectrum β-lactam (ESBL)-resistant enterobacteria from pigs reared in Enugu State Southeast, Nigeria and determine the antibacterial resistance profile of the isolates. Rectal swabs were collected from 190, randomly selected, apparently healthy pigs. Isolation of ESBL-resistant enterobacteria was done using Mac Conkey agar supplemented with 2 µg/ml of cefotaxime. Phenotypic characterization of the isolates to generic level was done following standard biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…Susceptibility profile of ESBL producing organisms recovered from cattle feces The genus Salmonella were the highest producers of ESBL in the current study. In a previous study evaluating rectal swabs of pigs in Nigeria, Salmonella species ranked next to Klebsiella species in ESBL production (Ugwu et al, 2015). The finding is also in contrast to previous studies on human specimens in South, North-West and South-West Nigeria which observed Enterobacter species and Klebsiella species as the most prevalent producers of ESBL (Ogefere et al, 2015;Ogbolu et al, 2011;Yusuf et al, 2013).…”
Section: Detection Of Extended Spectrum Beta Lactamasecontrasting
confidence: 81%
See 1 more Smart Citation
“…Susceptibility profile of ESBL producing organisms recovered from cattle feces The genus Salmonella were the highest producers of ESBL in the current study. In a previous study evaluating rectal swabs of pigs in Nigeria, Salmonella species ranked next to Klebsiella species in ESBL production (Ugwu et al, 2015). The finding is also in contrast to previous studies on human specimens in South, North-West and South-West Nigeria which observed Enterobacter species and Klebsiella species as the most prevalent producers of ESBL (Ogefere et al, 2015;Ogbolu et al, 2011;Yusuf et al, 2013).…”
Section: Detection Of Extended Spectrum Beta Lactamasecontrasting
confidence: 81%
“…(22.2%) in South-East Nigeria (Duru et al, 2013;Ugwu et al, 2015). These discrepancies, in addition to paucity of data on the prevalence of ESBL among cattle in SouthSouth Nigeria necessitated the current study.…”
Section: Discussionmentioning
confidence: 93%
“…The variation in ampicillin resistance recorded in these studies could be related to differences in usage of ampicillin in the various study areas . Ampicillin is not known to be a drug of choice in small animal medicine in Nigeria, but it is frequently used in humans (alone or in combination with cloxacillin) and food-producing animals (Chah and Nweze, 2001;Ugwu et al, 2015). Thus, these factors could also have contributed to high ampicillin resistance observed in this study (Ljungquist et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…The high rate of extended-spectrum β-lactam resistance in this study may be as a result of frequent use of extended-spectrum β-lactams in small animal medicine in Nigeria. Moreover, extended-spectrum β-lactams are also frequently used in Nigerian hospitals, and high prevalence of ESBL-resistant organisms in food animals, is a good indication that the drugs are used in these animals in the country Ugwu et al, 2015). Thus, many potential sources of ESBLs genes existed, acquisition of the genes by the isolates might have been facilitated by poor personal and public hygiene in Nigeria (Woerther et al, 2013;Schaufler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation